ENT 530 Social Media Portfolio / Muhammad Ikhwan Sobri - Sobri, Muhammad Ikhwan (2019)
This business was started on 25 September 2019,a few day after we got our certificate for Suruhanjaya Syarikat Malaysia(SSM). This business was idea from my family and all of my family members involve in my business. The name of our business is FL Mamavellous Bakery which it FL is our mother name Fauziah Lockman and mamavellous is combination of mama and marvelous. This is because our cookies was homemade and the recipe was from our mother. Furthermore, we also feel that the taste of our cookies will make our customer feel marvelous and happy we they eat our cookies. We use our own house at Kampung Manis, Perai, Pulau Pinang as our business premise because of this was strategic place for us and we can save our budget for rental other premise. Beside that, we only sale our product by delivery. So there no need cost to decorate our premise to attract the customer.All delivery was free of charge inside the town of Perai and outside that we will charge base on the distance.